Measures for sustainable management on the natural resources in the target villages. - China. Guizhou Academy of Agricultural Sciences ([Date of publication not identified])
In intervention phase, the general objectives for sustainable management on natural resources in target villages are to develop and utilize the natural resources resonablely and to enforce effective management rigorously in order to reach food security and enhance the villagers' welfare.
1. Objectives -- 1.1. General objectives -- The specific objectives include -- 1.2. Main economic index -- 2. Basic intervention measures -- 2.1. Propagating and conducting relevant laws and regulations of conserving natural resources, strengthening villagers' sense of legal system to conserve and rationally use natural resources so as to consolidate the resource management by law -- 2.2. Formunating and perfecting the local stipulations is an important measure for protecting natural resources in near future -- 2.3. Setting up and strengthening the administrative agence, enforcing the function of basic commjunity organization in natural resource management -- 2.4. Building up natural resource development funds for village groups -- 2.5. Spreading cultural and scientific knowledge among the people, improving their living condition and leading the villagers to set up a scientific, healthful and civil way of life -- 3. Classified intervention measures -- 3.1. Plough lands -- 3.2. Forest land -- 3.3. Grass land -- 3.4. Biological resource -- 3.5. Water resource.
Typescript.
IDRC funded project.
Community-based natural Resource Management in the Mountainous Area of Guizhou Province (China).
Keywords: Management -- Natural resources